ASSESSMENT OF THE IMPACT OF ROAD SURFACE IRREGULARITIES ON ELECTRIC VEHICLE PASSABILITY CHARACTERISTICS - Begmatov Baxriddin; Normatov Javokhir; Qo‘chqorov Jahongir (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This thesis analyzes the influence of road surface irregularities on vehicle passability characteristics. It highlights the impact of road deformations, potholes, and uneven surfaces on traffic safety, driving speed, fuel consumption, and operational efficiency of vehicles. During the research, dynamic loads occurring during vehicle movement on uneven roads and their effects on vehicle components were evaluated. In addition, the relationship between road quality and vehicle passability indicators was scientifically substantiated.